1992
DOI: 10.2134/agronj1992.00021962008400010006x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on Cotton Fruit Retention

Abstract: Temperature is a major environmental factor that affects cotton (Gossypium hirsutum L.) production. Temperatures of 35 to 40°C are frequently observed in cotton‐producing areas. High‐temperature environments are sometimes associated with cotton sterility and boll retention problems; however, there is little specific information available on cotton sensitivity to temperature. We conducted a series of experiments in naturally lit growth chambers where the temperature was accurately controlled so we could measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 11 publications
2
76
1
3
Order By: Relevance
“…The number of bolls retained on the cotton plant was very strongly controlled by temperature regimens (Reddy et al 1999). The optimum temperature for boll retention is 28 °C and the young bolls are shed when the average daily temperature exceeds the optimum, with a longer the exposure to above-optimum temperatures resulting in a higher frequency of boll abscission (Reddy et al 1992(Reddy et al , 1999. In the cottongrowing areas of China, especially the Yangtze River valley, several episodes of high temperatures greater than 35 °C usually occur in July and August, a period when cotton flowering and boll loading are in their developmental phases, resulting in the abscission of bolls and a reduction of lint yield (Zhou et al 1996;Miao et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of bolls retained on the cotton plant was very strongly controlled by temperature regimens (Reddy et al 1999). The optimum temperature for boll retention is 28 °C and the young bolls are shed when the average daily temperature exceeds the optimum, with a longer the exposure to above-optimum temperatures resulting in a higher frequency of boll abscission (Reddy et al 1992(Reddy et al , 1999. In the cottongrowing areas of China, especially the Yangtze River valley, several episodes of high temperatures greater than 35 °C usually occur in July and August, a period when cotton flowering and boll loading are in their developmental phases, resulting in the abscission of bolls and a reduction of lint yield (Zhou et al 1996;Miao et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that young bolls abscise when exposed to average daily temperatures above 28°C and the longer the exposure to the above-optimum temperature, the higher the abscission frequency (Reddy et al 1992). At present, climatic changes are a major concern to agriculturalists throughout the world.…”
mentioning
confidence: 99%
“…Boll retention is complex and can be affected by many interacting factors such as genetics, physiology, nutrition, water stress, temperature, competition for photosynthates, insects or a combination of any of these [3] [13] [14] [15] [16]. These same factors can also affect boll weight.…”
mentioning
confidence: 99%
“…The sensitivity of FC to changing temperatures was estimated using a literature-derived SF on a scale of 1 to 3 to represent general thermal sensitivities where crops classified as 1 are the (Reddy et al 2005;Oosterhuis 1999); 20-32°C (Burke et al 1988;Reddy et al 1991); 28-32°C (pollination; (Brown 2008;Snider et al 2011)); T failure = 35°C (Reddy et al 1992(Reddy et al , 1997 Rice Oryza sativa T opt = 23-26°C (Baker et al 1995;Horie et al 2000); T failure = 35°C (Baker et al 1995) Wheat Triticum T opt = 20-30°C (Fageria 1992); T max = 35°C (Torabi et al 2015) Thermal range (TR) is the summer maximum temperature where 95% of the crop was cultivated in 2012 with analyses reflecting changes in 2012 area and potential cultivation area.…”
Section: County-level Impact Assessmentmentioning
confidence: 99%